Occupational burnout in health care – analysis of systemic and organisational risks as well as possible preventive actions - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula; Ślazyk-Sobol, Magdalena; Lehesvuori, Minna; Polak, Angelika (Wypalenie zawodowe w opiece medycznej – analiza zagrożeń systemowo-organizacyjnych oraz możliwych działań prewencyjnych, 2019)
The article presents the risk of occupational burnout observed in health care, as well as possibilities of prevention in this regard. Its authors used their knowledge and experience obtained during the implementation of the international Time2Grow project financed from the European Social Fund. The project was dedicated to developing a burnout prevention model mainly in the area of broadly understood health care. The project was implemented in the Polish-Belgian-Finnish partnership, thanks to which it provided great opportunities to benefit from good European practices. The article presents the results of quantitative primary research carried out on Poland in the group of nurses and midwives, as well as selected results of quantitative and qualitative research conducted in Finland on a group of practicing nurses caring for elderly people
Econometrics = Ekonometria, 2019, Vol. 23, No. 4, s. 43-62
Keywords: burnout prevention; health care; primary research results; prewencja wypalenia zawodowego; opieka medyczna; wyniki badań pierwotnych; wypalenie zawodowe